2002
DOI: 10.1136/heart.88.1.52-a
|View full text |Cite
|
Sign up to set email alerts
|

Thrombus after transcatheter closure of ASD with an Amplatzer septal occluder assessed by three dimensional echocardiographic reconstruction

Abstract: Aims: To investigate the hypothesis that changes in the ECG over time may be an important and readily available marker of prognostic value in patients with heart failure. Methods: 112 elderly patients (81 men) with stable heart failure, a mean (SD) age of 73.3 (4.4) years, left ventricular ejection fraction 38 (17)%, and peak oxygen consumption 15.1 (4.7) ml/kg/min had ECG measurements on two occasions a minimum of 12 (5) months apart. Results: During the subsequent follow up period (mean 27 (17) months) 45 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 8 publications
0
16
0
1
Order By: Relevance
“…If more than 6 months is necessary for complete neoendocardial coverage of both the right and left atrial discs, the risk of thrombus formation persists after the standard 6 months of antiplatelet therapy has been concluded. Different authors have reported cases of thrombus formation on the device more the 6 months after ASD transcatheter closure [4,5]. The question is, how long must antiplatelet therapy last after transcatheter ASD closure.…”
mentioning
confidence: 99%
“…If more than 6 months is necessary for complete neoendocardial coverage of both the right and left atrial discs, the risk of thrombus formation persists after the standard 6 months of antiplatelet therapy has been concluded. Different authors have reported cases of thrombus formation on the device more the 6 months after ASD transcatheter closure [4,5]. The question is, how long must antiplatelet therapy last after transcatheter ASD closure.…”
mentioning
confidence: 99%
“…This complicated, firstgeneration device has been abandoned with the increased availability of new generation, self-centering occluder systems that allow a user-friendly and easy implantation. However, device thrombosis has been reported with virtually any available occluder system including not only the ASDOS device [19,25,26,27], but also CardioSEAL/Starflex [14,17,28,29], Angle Wings [15,17], buttoned device [8], Clamshell [10], Helex [17], PFO-Star/CardiaStar [11,12,17,30] and Amplatzer device [17,22,30,31]. Most of these studies represent case reports and no randomized study has been published.…”
Section: Thrombus Formation: Detection and Risk Factorsmentioning
confidence: 97%
“…Once device thrombosis has occurred, medical treatment options include systemic anticoagulation therapy with heparin [22,31] or warfarin [14], the use of GP IIa/IIIb antagonists in conjunction with thrombolytic [29] or heparin therapy [32]. Again, there are no randomized reports available to assess the effectiveness of any of these treatment strategies against the others.…”
Section: Thrombus Formation: Detection and Risk Factorsmentioning
confidence: 98%
“…Thrombus developed on eight different types of transcatheter devices. All commercially available devices had at least one reported case of thrombosis: PFO-Star (17 patients) [4,5,8,15], ASDOS (13 patients) [5,7,[13][14][15], CardioSEAL Starflex (9 patients) [5,12,18,20], CardioSEAL (5 patients) [5,9,16,17,19], Angel Wings (4 patients) [5,17], Amplatzer (4 patients) [5,6,10,15], Buttoned (1 patient) [11], and Helex (1 patient) [5]. Patient age was available in half of the cases (mean age, 44.2 Ϯ 9.8 years).…”
Section: Thrombus Informationmentioning
confidence: 99%